Glucolipotoxicity induces endothelial cell dysfunction by activating autophagy and inhibiting autophagic flow. (10th May 2022) - Liu, Yulan; Xiang, Hong; Xiong, Wenfang; Ouyang, Jie; Liu, Hengdao; Zhao, Shaoli; Xiao, Jie; Li, Jialing; Shu, Zhihao; Wang, Xuewen; Liu, Huiqin; Zhang, Jing; et al.
Objectives: This study aims to determine the role and mechanism of autophagy in endothelial cell dysfunction by glucolipotoxicity. Methods: Human umbilical vein endothelial cells (HUVECs) were treated with high glucose and high palmitic acid. The number of autophagosomes was evaluated by monodansylcadaverine (MDC) staining and transmission electron microscopy (TEM). The expression of autophagy-related proteins (LC3 and P62) was assessed by Western blotting. Capillary tube-like formation was evaluated on Matrigel. Reactive oxygen species (ROS) production was detected by DCFH-DA. Cell apoptosis was measured by Hoechst 33258 staining and flow cytometry. Phosphorylation of AMPK, mTOR, and ULK1 was also analyzed by Western blotting. Results: We found that glucolipotoxicity induced autophagy initiation and hindered autophagosomes degradation. Moreover, glucolipotoxicity increased the production of intracellular ROS, decreased the ability of tubular formation, and increased cell apoptosis. However, endothelial cell dysfunction was alleviated by 3-methyladenine, an early-stage autophagy inhibitor. Additionally, glucolipotoxicity promoted the phosphorylation of AMPK and ULK1 and inhibited the phosphorylation of mTOR. Conclusions: Glucolipotoxicity initiates autophagy through the AMPK/mTOR/ULK1 signaling pathway and inhibits autophagic flow, leading to the accumulation of autophagosomes, thereby inducing apoptosis and impairing endothelial cell function.